Filsafat Pendidikan Perenialisme Terhadap Pengembangan Kurikulum Pendidikan Agama Islam di Era Modern - Mutiara Mahardika; Rana Meiyanda; Wahyu Ashabul Jannah; Amrullah; Fakhruddin (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the relevance of perennialism educational philosophy to the Islamic Religious Education curriculum. The research is motivated by the emergence of various moral crises, individualism, hedonism, and the decline of spiritual awareness in modern education, which require the strengthening of moral and spiritual values within the educational process. This study employed a qualitative approach using library research methods. The research data were obtained through documentation studies of various primary and secondary sources related to perennialism philosophy and the Islamic Religious Education curriculum. Data analysis was conducted using content analysis techniques through stages of data organization, categorization, interpretation, and conclusion drawing using deductive and inductive approaches. The results of the study indicate that perennialism educational philosophy has strong relevance to the Islamic Religious Education curriculum, particularly in the aspects of educational objectives, learning materials, teaching methods, and character building. Perennialism emphasizes the importance of universal and eternal values as the foundation of education in shaping moral, wise, and spiritually aware individuals. These values are aligned with the objectives of Islamic Religious Education, which focus on developing faith, piety, and noble character. In addition, learning methods such as role modeling, habituation, and moral reflection are considered consistent with the principles of perennialist education. This study provides theoretical contributions to the development of Islamic educational philosophy studies as well as practical contributions to the development of Islamic Religious Education curricula and learning processes that are more oriented toward strengthening students’ character and spirituality.